Has the Euro changed the Business Cycle? - Zeno Enders; Gernot J. Müller (Oesterreichische Nationalbank (OeNB), 2010)
In this paper we analyze European business cycles before and under EMU. Across the two periods we find 1) a significant decline in real exchange rate volatility, 2) significant changes in cross-country correlations, and 3) the volatility of macroeconomic fundamentals largely unchanged. We develop a two-country business cycle model and show that the calibrated model is able to replicate key features of the data prior to and under EMU.We find that the euro has a strong bearing on the transmission mechanism as cross-country spillovers increase substantially under EMU. As a result, foreign shocks become more and domestic shocks less important in accounting for the (unchanged) volatility of macroeconomic fundamentals.
Keywords: F41; F42; E32; 330; European business cycles; Euro; Optimum Currency Area; EMU; Monetary Policy; Exchange rate regime; Cross-country spillovers